BITUMEN SEEPAGE AND ITS EFFECTS ON BIODIVERSITY IN ONDO STATE, NIGERIA (2013)
Biodiversity enhances capacity of ecosystems to provide food resources and sequestration services of pollutants in soil and water. Bitumen seepage could impact negatively on soil and vegetation, thereby reducing their value. Information on the impact of bitumen seepage on the abundance of biodiversity in Nigeria is scanty. In this study, effects of bitumen seepage on biodiversity were therefore investigated. The study was conducted in bitumen belt of Ondo state for three years, with and without evidence of bitumen seepage in Ode-Irele and Ebute-Irele respectively. Composite samples of soil and foliar tissues of six most commonly occurring plants: Panicum laxum, Panicum maximum, Lycopodium cernuum, Calopogonium mucunoides, Pteridium aquilinium and Centrosema molle were collected from experimental sites and analysed for presence of heavy metals (copper, zinc, lead, chromium, cadmium, nickel and arsenic) using standard procedure. Water samples at depth of 30 cm midstream were collected for physicochemical analysis: (sulphate, Chemical Oxygen Demand (COD) and turbidity analysis) using standard methods. Vegetation cover was sampled using 5m x 5m sample plots for trees ( ≥10 cm diameter at breast height) and shrubs, while 1m x 1m sub-plot was used for herbs. Point count and line transect methods were used to enumerate birds and other wild animals respectively. Flora and fauna diversities on experimental sites in wet and dry seasons were assessed using Shannon-Wiener (H1) and Simpson (D) indices. Data were analysed using descriptive statistics and t-test at p=0.05. In soil, significantly lower values of copper (139.6 ± 73.8mg/kg) and zinc (219.7 ± 106.1mg/kg) were in polluted sites compared with values in control. In foliar tissues, higher levels of lead (4.0 ± 0.8mg/kg); chromium (11.9 ± 1.9mg/kg); cadmium (2.2 ± 3.4mg/kg); nickel (21.2 ± 3.0mg/kg); and arsenic (0.4 ± 0.3mg/kg) were average values found in combinations of all the plants considered namely P. laxum, P. maximum, L. cernuum, C. mucunoides, P. aquilinium and C. molle in seepage sites compared with values in control. Water on seepage site had significantly higher values of sulphate (6.0 ± 0.8mg/L), COD (553.6 ± 343.7mg/L), and turbidity (19.3 ± 12.0 NTU) than those in control. Number of different species of shrubs (797.0 ± 198.6/ha), herbs (29999.9 ± 5798.8/ha), birds (14.2 ± 9.3/ha), and terrestrial wildlife (60.3 ± 11.6/ha) in seepage site were significantly lower than that in control [(2799.8 ± 1195.9/ha), (69977.8 ± 18298.9/ha), (49.6 ± 15.6/ha) and (140.3±32.6/ha) respectively]. Raphia longiflora (H1=0.33, D=0.01), Chromolaena odorata (H1=0.52, D=0.05), Ageratum conyzoides (H1=0.44, D=0.02), Cinnamopteryx castaneofuscus (H1=0.56, D=0.06) and Achatina spp (H1=0.68, D=0.18) had highest abundance in the study area. Seasonal abundance of herbs (541,666.7 ± 409899.9/ha), birds (166.4 ± 60.4/ha), and other wild animals (336.7 ± 223.9/ha) on experimental sites in wet season was significantly higher than that of dry season. At the end of the three years study, heavy metals in plants and pollutants in water were high in bitumen seepage area. There were declines in diversities of birds, other wild animals and flora caused by bitumen seepage.